Fabrication of nanostructured Fe-Co alloy powders by hydrogen reduction and its magnetic properties - Lee, Young Jung; Lee, Baek-Hee; Kim, Gil-Su; Lee, Kyu Hwan; Kim, Young Do (PROGRESS IN POWDER METALLURGY, PTS 1 AND 2, 2007)
Magnetic properties of nanostructured materials are affected by the microstructures such as grain size (or particle size), internal strain and crystal structure. Thus, it is necessary to study the synthesis of nanostructured materials to make significant improvements in their magnetic properties. In this study, natiostructured Fe-20at.%Co and Fe-50at.%Co alloy powders were prepared by hydrogen reduction from the two oxide powder mixtures, Fe2O3 and Co3O4. Furthermore, the effect of microstructure on the magnetic properties of hydrogen reduced Fe-Co alloy powders was examined using XRD, SEM, TEM, and VSM.